2012
DOI: 10.1590/s0004-27302012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Lack of mutations in the leptin receptor gene in severely obese children

Abstract: Objective: To analyze the LEPR gene in obese children and to investigate the associations between molecular findings and anthropometric and metabolic features. Subjects and methods: Thirty-two patients were evaluated regarding anthropometric characteristics, blood pressure, heart rate, serum glucose, insulin, leptin levels, and lipid profile. The molecular study consisted of the amplification and automatic sequencing of the coding region of LEPR in order to investigate new mutations. Results: We identified a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…The LEPR gene, a member of cytokine-receptor family, is located on chromosome 1p31 and plays an important role in regulating body weight and energy expenditure (8, 9). Previous studies have shown that LEPR- K109R and -Q223R polymorphisms were risk factors of metabolic syndrome, including obesity (10-12), increased body weight and BMI (13), and an altered serum lipid profile (14), while the association between these two polymorphisms and NAFLD or coronary atherosclerosis were not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The LEPR gene, a member of cytokine-receptor family, is located on chromosome 1p31 and plays an important role in regulating body weight and energy expenditure (8, 9). Previous studies have shown that LEPR- K109R and -Q223R polymorphisms were risk factors of metabolic syndrome, including obesity (10-12), increased body weight and BMI (13), and an altered serum lipid profile (14), while the association between these two polymorphisms and NAFLD or coronary atherosclerosis were not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports linked it to some abnormalities, such as obesity and adiposity [2326], type 2 diabetes mellitus [27], peritonitis [28], susceptibility to enteric and respiratory disorders [2933], arteriosclerosis [34] and multiple forms of cancer [35–37]. However, other studies failed to show any association [3840].…”
Section: Introductionmentioning
confidence: 99%
“…Зокрема, ген лептинових рецепторів LEPR, який розташований у хромосомі 1p31, відіграє важли-ву роль в регуляції маси тіла, харчової поведінки, енергетичного гомеостазу та метаболічних проце-сів [5]. Ідентифіковано 6 алельних поліморфізмів гена LEPR -rs1137100 (K109R), rs1137101 (Q223R або Gln223Arg), rs1805134 (S343S), rs8179183 (K656N), rs1805096 (P1019P) та делеція/ вставка в пентанукле-отиді CTTTA в 3 -нетрансльованому сайті (3'UTR Del/Ins), однак їх поширеність та клініко-діагнос-тичне значення в різних етнічних групах є дискута-бельним [5,6]. У більшості досліджень відмічається зв'язок поліморфізму гену LEPR Q223R з факторами кардіоваскулярного ризику -ожирінням, метаболіч-ним синдромом, дисліпідемією [6][7][8].…”
Section: обґрунтування дослідженняunclassified
“…Ідентифіковано 6 алельних поліморфізмів гена LEPR -rs1137100 (K109R), rs1137101 (Q223R або Gln223Arg), rs1805134 (S343S), rs8179183 (K656N), rs1805096 (P1019P) та делеція/ вставка в пентанукле-отиді CTTTA в 3 -нетрансльованому сайті (3'UTR Del/Ins), однак їх поширеність та клініко-діагнос-тичне значення в різних етнічних групах є дискута-бельним [5,6]. У більшості досліджень відмічається зв'язок поліморфізму гену LEPR Q223R з факторами кардіоваскулярного ризику -ожирінням, метаболіч-ним синдромом, дисліпідемією [6][7][8]. Засвідчений зв'язок поліморфізму гена LEPR Q223R з розвитком серцевої недостатності у хворих на ІХС та дилята-ційну кардіоміопатію [9].…”
Section: обґрунтування дослідженняunclassified